FIG. 11 in King crabs up-close: ontogenetic changes in ornamentation in the family Lithodidae (Crustacea, Decapoda, Anomura), with a focus on the genus Paralomis - Hall, Sally; Thatje, Sven (Zenodo, 2010)
FIG. 11. — Southern Ocean Paralomis White, 1856 species: A, B, P. aculeata Henderson, 1888, holotype š CL 41 mm (BMNH 88.33), Prince Edward Islands; C, P. elongata Spiridonov, Türkay, Arntz & Thatje, 2006, ♀ CL 65 mm (collection S. Thatje, NOCS), Bouvet Island; D, P. anamerae Macpherson, 1988, ♀ CL 72 mm, MD24 Crozet Island, 655-700 m, IX.1980; E, F, P. formosa Henderson, 1888; E, paratype šCL 16.4 mm (BMNH 88.33), Rio Plata; F, š CL 72.6 mm (collection S. Thatje, NOCS), South Georgia groundfish survey; G, H, P. birsteini Macpherson, 1988, holotype ♀ CL 54.7 mm (USNM-228830); A, mid-branchial region, dorsal view; B, antero-lateral carapace, dorsal view; C, mid-branchial region, depicting significant intermoult wear on the tubercles, dorsal view; D, mid-branchial region, dorsal view; E, base of a lateral spine, showing secondary tubercles in juvenile specimen, dorsal view; F, mid-branchial region, not showing main spines, which are up to 10 mm in length, dorsal view; G, mid branchial region, dorsal view; H, mid-branchial tubercle, lateral view. Scale bars: A, C, E, G, H, 1 mm; B, 3 mm; D, F, 2 mm. : Published as part of Hall, Sally & Thatje, Sven, 2010, King crabs up-close: ontogenetic changes in ornamentation in the family Lithodidae (Crustacea, Decapoda, Anomura), with a focus on the genus Paralomis, pp. 495-524 in Zoosystema 32 (3) on page 511, DOI: 10.5252/z2010n3a10, http://zenodo.org/record/5167458